Medication Treatment With Methadone or Buprenorphine: Differential Reasons for Premature Discharge. Issue 2 (March 2019) - Proctor, Steven L.; Birch, Autumn; Herschman, Philip L.
Abstract : Objectives: Medication treatment with methadone or buprenorphine has shown demonstrated effectiveness for opioid dependence; while premature discharge is associated with adverse outcomes. Specific reasons for premature discharge generally fall into 2 broad categories (ie, patient- and program-initiated). Previous studies have typically failed to distinguish between different types of discharge reasons among patients who leave treatment early. This study sought to determine whether type of medication was associated with differential discharge reasons among medication treatment patients who were prematurely discharged. Methods: Data were derived from electronic health records for 5486 patients prematurely discharged from 41 for-profit licensed opioid treatment programs in the United States from 2012 to 2013. All patients were treated with methadone or buprenorphine. Patients were studied through retrospective chart review until premature discharge. Results: Buprenorphine patients who left treatment prematurely were 2.18 times (95% confidence interval [CI] 1.89–2.53) more likely to be discharged against medical advice relative to methadone patients after controlling for intake differences. Methadone patients were 1.76 times (95% CI 1.47–2.10) more likely to be administratively discharged after adjustment for covariates. Conclusions: Further research is warranted to determine whether individually-tailored strategies may improve retention for certain patients based on medication. Ongoing review of program rules and policies may benefit methadone patients, who are nearly twice as likely to be discharged for an administrative, program-initiated reason. Strategies including contingency management, motivational incentives, and psychoeducation regarding the advantages of retention may benefit buprenorphine patients who are over 2 times more likely to leave treatment early due to a patient-initiated reason.